Gender difference analysis of Xp11.2 translocation renal cell carcinomas’s attack rate: a meta-analysis and systematic review - Wenyuan Zhuang; Ning Liu; Hongqian Guo; Chunni Zhang; Weidong Gan (BMC Urology, 2020)
Abstract Background Xp11.2 translocation renal cell carcinoma (tRCC) is recently recognized. As Xp11.2 tRCC involved gene translocation and fusion in X chromosome and the number of X chromosomes in female is twice of male, we wondered whether the gender difference of attack rate is consistent with the proportion of the X chromosome. Methods : In the present paper, meta-analysis was performed to find out the difference of morbidity between male and female. Results Nine studies with 209 cases calculated. Odds ratios (ORs) and ORs with 95% confidence intervals (CIs) were calculated for attack rate of Xp11.2 RCC with different gender. The result showed that the attack rate of female was higher than that of male with pooled OR of 2.84 (95% CI = 1.48–5.45), while the rate rises even further in adult (OR = 3.37, 95% CI =2.19–5.18). In other types of common kidney cancer, the OR value is less than 1, which means that the incidence of female is lower than that of male. Conclusions The result showed that the incidence rate of female patients is much higher than that of male patients with Xp11.2 tRCC, it was reasonable to indicate that this particular incidence rate is related to the X chromosome.